Cardiac Inflammatory Myofibroblastic Tumours in Three Young Adult Cats. (November 2022) - Machida, Noboru; Hirakawa, Atsushi; Kanno, Nobuyuki; Hori, Yasutomo
Summary: Inflammatory myofibroblastic tumours (IMTs) of the heart are described in three young adult cats (case 1, 3.5 years old; case 2, 2.7 years old; case 3, 1.8 years old) that died due to pleural and pericardial effusions resulting from congestive heart failure. At necropsy, cardiac masses, measuring 4 × 3 × 2.5 cm (case 1), 3.5 × 2.5 × 2 cm (case 2) and 3 × 2.5 × 2 cm (case 3), were located mainly in the right auricle (case 1) and atrial septum (cases 2 and 3) with variable extension into the surrounding tissue. Histologically, the atrial masses in all three cats comprised proliferation of spindloid mesenchymal cells and an inflammatory infiltrate of plasma cells and lymphocytes in variable amounts of myxoid background. The spindloid cells were uniform and characterized by pale eosinophilic cytoplasm and a vesicular nucleus containing prominent nucleoli, with no remarkable cytological atypia or mitotic activity. Immunohistochemically, these cells were positive for vimentin and α-smooth muscle actin in all cases, supporting a myofibroblastic origin. The histopathological and immunohistochemical features were consistent with those of IMTs in humans and animals. There have been no previous reports of such tumours occurring in the heart of the cat.